Development of 3D Animation in AR-based Children's Storybooks - Lukcyhasnita, Andam; Khairina, Isni; Siregar, Rumnasari K (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
Along with the advancement of technology, it brings updates in the digital world, namely the reality of the additional world or Augmented Reality (AR). The application of AR has now been applied in various fields, especially in education. This is because the presence of AR makes the learning process fun. One of the basic learning is reading. However, unfortunately sometimes reading through book media becomes quite boring. For children, now the use of smartphones has become something close and common, so that reading books becomes less interesting because it only displays still images. Therefore, this study was conducted to create an interesting book by combining AR technology. The use of this technology aims to develop children's story books based on Augmented Reality (AR) with 3D animation to increase literacy interest in children aged 6-8 years. This study has succeeded in creating a children's story book entitled The Adventures of Budi and Wati, as well as a mobile application with Android OS and has successfully displayed 3D animation from book illustration images. In this study, data collection was used with literature studies in various sources. The process of creating this 3D animation was carried out in 3 stages of production. Pre-production, Production, and Post-production. In the pre-production stage, the research team carried out story idea and script preparation activities, in the production process, the development process, 3D animation development and AR application development were carried out. In the post-production stage, the product trial process was carried out on several devices. The results showed that the application could be run, but on Android products with OS version 14. Even so, the application product can run well on Android OS 14 and display animations smoothly. AR technology presents characters and stories in interactive visual form, so that children are more enthusiastic about getting involved in reading. The application of this technology not only encourages reading interest, but also stimulates children's creativity and imagination through a more enjoyable and immersive reading experience.